Margarita Barajas Tinoco, Silvia Figueroa Ramírez y José Ascención Moreno Mena (Coords.), Casinos del desierto, juegos de azar y apuestas, México, Universidad Autónoma de Baja California, 2019, 270 pp. - Cesar Jiménez-Yañez (Perfiles Latinoamericanos)
Consultar texto.